Synthesis and application of Al trimesate-based metal-organic framework: a critical review - Zheng, Huifang; Chen, Qian; Chen, Zhijie; Ni, Bing-Jie (Frontiers in Environmental Engineering, 2024)
This review comprehensively explores the synthesis and diverse applications of the Al trimesatebased metal-organic framework, MIL-96 (Al). It begins with an introduction to the structure and properties of MIL-96 (Al), followed by an in-depth discussion of various synthesis strategies, including hydrothermal, microwave irradiation, electrochemical, mechanochemical, and sonochemical methods. The paper then delves into environmental remediation applications, highlighting MIL-96 (Al)'s effectiveness in fluoride and heavy metal removal, as well as in the elimination of volatile organic compounds (VOCs) and CO2. The review further examines the role of MIL-96 (Al) in catalysis and its emerging significance in battery technology, showcasing its versatility and potential in sustainable energy solutions. Finally, the paper concludes with perspectives on future research directions, emphasizing the ongoing development and optimization of MIL-96 (Al) for environmental and energy-related applications.